2011
DOI: 10.1088/0022-3727/44/14/145206
|View full text |Cite
|
Sign up to set email alerts
|

Plasma kinetics in ethanol/water/air mixture in a ‘tornado’-type electrical discharge

Abstract: This paper presents the results of a theoretical and experimental study of plasma-assisted reforming of ethanol into molecular hydrogen in a new modification of the "tornado" type electrical discharge.Numerical modeling clarifies the nature of the non-thermal conversion and explains the kinetic mechanism of nonequilibrium plasma-chemical transformations in the gas-liquid system and the evolution of hydrogen during the reforming as a function of discharge parameters and ethanol-to-water ratio in the mixture. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 44 publications
(50 reference statements)
1
30
0
Order By: Relevance
“…As already mentioned, the plasma effect induced by electron collisions mainly contributes to the generation of primary radicals in the initial reaction step. At this point, the reaction pathway is determined by the energy levels of the electrons participating in collisions; the threshold energy levels for Equation – are shown below CnormalH3OH+eCnormalH3O+H Eth=7.95 eV CnormalH3OH+eCnormalH3+OH Eth=8.28 eV CnormalH3OH+eCnormalH2OH+H Eth=8.28 eV …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As already mentioned, the plasma effect induced by electron collisions mainly contributes to the generation of primary radicals in the initial reaction step. At this point, the reaction pathway is determined by the energy levels of the electrons participating in collisions; the threshold energy levels for Equation – are shown below CnormalH3OH+eCnormalH3O+H Eth=7.95 eV CnormalH3OH+eCnormalH3+OH Eth=8.28 eV CnormalH3OH+eCnormalH2OH+H Eth=8.28 eV …”
Section: Discussionmentioning
confidence: 99%
“…At this point, the reaction pathway is determined by the energy levels of the electrons participating in collisions; the threshold energy levels for Equation (13)- (15) are shown below. [26,27] CH 3 OH þ e ! CH 3 O þ H E th ¼ 7:95 eV ð13Þ…”
Section: Hydrocarbon Formation By Primary Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full mechanism developed for this experimental work is composed of 30 components and 130 chemical reactions between them and its closed to [11]. The charged particles (electrons and ions) are ignored in the mechanism, because of low degree of ionization of the gas (~ 10 −6 -10 −5 ).…”
Section: Model and Calculationsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] As highly reactive transient intermediates, HO 2 radical plays an important role in the atmospheric oxidation, [16] hydrocarbon fuel combustion reaction, [17] atmospheric photo-chemical reaction, [18] and some very important biochemical reactions. [19] As an important reaction with HO 2 radical and C 2 H 5 O radical, [20,21] it is of great significance to the study of atmospheric chemistry. It has been suggested that the further oxidation of CH 3 O and CH 2 OH radicals by HO 2 produces more stable species like formaldehyde, formic acid, or hydrogen peroxide Equations 3 to 5.…”
Section: Introductionmentioning
confidence: 99%